Role of Women In Decision Making Process and Other Family Programs: Examining the Decision-Making Dynamics in Local Governance (Journal of Advances and Scholarly Researches in Allied Education, 2012)
reveals that 137 respondents opinedthat PRI decision are taken as per rule, i.e. voting system, followed by 34(15.18%) respondents who have no clear idea about the decision making process.While 53 (23.66%) responded that all the decision are taken unanimously.Similarly at the Gram Panchayat level 20 (14.09%) Panches, 4 (26.67%)Sarpanches and 10 (16.95%) Panchayat Samiti members did not response to it. Itmeans they act as a person of just thumb impression or signing on paper aboutthe consensus of final decision taken by other member of the Panchayat.Majority of 99 (69.72%) Panches and 8 (53.33%) Sarpanches opined that all thedecisions are taken as per the rules like casting of vote. 6 (75.00%) ZilaParishad member responded that maximum of decision taken through the process ofcasting vote. So on the basis of above data that decisions are taken either byvoting or by Unanimity.